1997
DOI: 10.1093/genetics/146.4.1333
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Inducible Repair-Recombination System in the Female Germ Line of Drosophila melanogaster. III. Correlation Between Reactivity Levels, Crossover Frequency and Repair Efficiency

Abstract: We previously reported evidence that the so-called reactivity level, a peculiar cellular state of oocytes that regulates the frequency of transposition of I factor, a LINE element-like retrotransposon, might be one manifestation of a DNA repair system. In this article, we report data showing that the reactivity level is correlated with the frequency of crossing over, at least on the X chromosome and on the pericentromeric region of the third chromosome. Moreover, a check for X-chromosome losses and recessive l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 17 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…We investigated the impact of parental age on the lifespan of D. melanogaster using two strains here named A and B , which were examined as part of a larger study (see materials and methods, [ 33 , 34 ]) with the experimental setup shown in Figure 1B . The average parental age was 4 ± 2 days for the SG isolines and 40 ± 2 days and 20 ± 2 days, respectively for A and B , for the LG isolines ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…We investigated the impact of parental age on the lifespan of D. melanogaster using two strains here named A and B , which were examined as part of a larger study (see materials and methods, [ 33 , 34 ]) with the experimental setup shown in Figure 1B . The average parental age was 4 ± 2 days for the SG isolines and 40 ± 2 days and 20 ± 2 days, respectively for A and B , for the LG isolines ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%